Public perceptions of flash floods in Kelantan: causing by topography or climate change / Nur Aliesya Athirah Suhaimi and Ruwaidah Borhan - Suhaimi, Nur Aliesya Athirah; Borhan, Ruwaidah (2024)
Flashfloods is one of the most common natural disaster and circumstances beyond one’s control which causes severe damage to the nature life, properties, and human well-being. The topography itself usually play an important role in controlling the climate change. However, it happens beyond of our control and became the main or annual natural disaster in Kelantan. Kelantan was selected in this case study due to the record setting flood in 2014 where the floods turn into ‘tsunami-like disaster’. Natural Disaster Management Agency (NADMA), The Malaysian Meteorological Department (Met Malaysia) website and secondary data which included a direct interview of local people were used to evaluate the flood risk area and the factor that occur in this disaster. However, several districts have been identified as the most flood-affected areas in Kelantan which include the district of Gua Musang, Kuala Krai and Rantau Panjang. This paper is focus on studying to determine between the two factors that cause floods in Kelantan, either topography or climate change or both are related to. Due to the survey conducted during two days in Kelantan, the result shows that respondent answered has plunged into both topography and climate change are related based on the issue arises and discussed with the respondents.